Influence of aerated irrigation using brackish water on transport of water, nitrogen, and salt in saline soil in the Yellow River Delta - DAI Kuiguan; WANG Mengmeng; LI Bo; ZHU Ziguo; SUN Chitao; ZHANG Peng; WANG Junhui; WANG Haocheng; ZHANG Qian (Guan'gai paishui xuebao)
【Objective】Aerating irrigation water is a technique to avoid anaerobicity when irrigating low-permeable soils. In this paper, we study the impact of aerated irrigation with brackish water on water transport, nitrogen transformation, and salt movement in salt-alkali soils in the Yellow River Delta.【Method】The experiment consisted of irrigation with aerated freshwater, brackish water, and a mixture of freshwater and brackish water. The control was irrigation with freshwater without aeration. In each treatment, we measured the cumulative infiltration amount, advancement of the wetting fronts, soil water content, soil salt content, and soil nitrogen content.【Result】Compared with CK, irrigation with brackish water increased the cumulative infiltration amount and the advancement of the wetting front by 10.77% and 20.38%, respectively, 100 minutes after the irrigation, and by 54.58% and 59.77%, respectively, 600 minutes after the irrigation. Compared with aerated irrigation with freshwater, brackish water irrigation increased the cumulative infiltration and the advancing of the wetting front by 26.67% and 72.43%, respectively, 100 min after the irrigation, and 66.1% and 72.43%, respectively, 600 mins after the irrigation. Brackish water irrigation reduced salt content at the depth of 60 cm by more than 20.8%, compared to freshwater irrigation. Compared with CK, aerated irrigation with both freshwater and brackish water significantly increased ammonium content at the depth of 40 cm, particularly with brackish water. Following irrigation, ammonium content continuously increased for seven days, reaching a peak before decreasing. Brackish water irrigation increased nitrate content at the depth of 60 cm. Overall, nitrate content increased after irrigation, peaking 21 days later.【Conclusion】Aerated irrigation using brackish water increased soil moisture content and improved soil desalination. Aerated irrigation using brackish water and freshwater both improved ammonium content at the depth of 40 cm, while brackish water irrigation enhanced nitrate content at the depth of 60 cm.